The nature, objectives and problems of the elementary on-campus student teaching program, Institute of Education, Far Eastern University - Peralta, Nelly Quinones 1943- (s.n.], 1967)
This study presents the nature, the objectives, and the problems of the elementary on-campus student teaching program of the Institute of Education, Far Eastern University in an attempt to identify the problems of the student teachers on-campus and those involved in the program as a whole for the second semester 1966-1967.